Developing a smartphone app with UK migrants for UK migrants: lessons learned from focus group work. (30th September 2020) - Burns, R; Hugenholtz, G C G; Kirkby, V; Elsay, N; Aldridge, R W
Abstract: Background: In 2018, 14% of people living in the UK were born abroad, yet we have a limited understanding of the broader determinants of their health. To address this knowledge gap, the Health on the MovE (HOME) smartphone application (app) study was conceived. Through app-based surveys, the study will examine how risk factors for health and well-being are distributed among migrants and how these vary over time since migration to the UK. There is a lack of research addressing the development of apps for longitudinal data collection in the general population - and we did not find any in migrant groups. Methods: To better inform the design of the HOME app study, three workshops were held in 2018 and 2019, involving both migrants and App development experts. We used a semi-structured interview schedule focused on five themes: smartphones, apps and research, HOME app wireframe (screen-by-screen review of the app), types of surveys and survey schedules, resource section content, and participant engagement strategies. The participants were purposively sampled to reflect the migrant population arriving in the UK from non-EU countries. Results: Migrants reported high smartphone use and were positive about the app design and app-based research. Concerns around privacy and data protection were highlighted and limits were suggested for the frequency of surveys and the number of questions used. Mental health was identified as a key topic for research. Participants requested the inclusion of resources concerning asylum claim procedures and immigrant and labour laws. Migrants advised that study recruitment material should clearly state the purpose and scope of the research and requested regular feedback on study outcomes. Conclusions: The workshops provided important feedback and facilitated the co-production of the HOME app. Overall findings suggest that the study would be both acceptable to the migrant population and feasible for real-time data collection. Key messages: The process identified potential barriers to the acceptability and feasibility of an app-based study for real-time data collection in the UK migrant population. Organising workshops with migrants allowed for an iterative process of co-production of the HOME app. Their critical comments resulted in subsequent changes to the app design and study methodology.